Assessing water use, energy use and carbon emissions in lift-irrigated areas: a case study from Karshi steppe in Uzbekistan - Djumaboev, Kakhramon; Yuldashev, Tulkun; Holmatov, B.; Gafurov, Zafar (Wiley, 2019)
The advantages of a nexus approach in addressing complex environmental challenges are becoming increasingly clear. In Central Asia, however, the nexus between water–food–energy has not received adequate attention, as the very few studies that have been conducted fell short of quantifying nexus trade-offs and benefits at a practical, small scale. This paper applies a quantitative accounting method to assess water and energy use intensity in irrigated areas of the Karshi Steppe of Central Asia that are supplied by pumping water uphill (lift-irrigated) from the underlying river. The results indicated that the potential water and energy savings as well as the greenhouse gas (GHG) emission reductions could be achieved by applying an optimal planning deficit irrigation schedule simulated using CROPWAT 8. Some 575 MCM (million cubic metres) of water and 259 GWh of electricity can be saved, while the CO2 equivalent emissions can be reduced by almost 122 000 t. Achieving these savings requires a mix of technical and policy components. This paper describes an example of proper irrigation planning as a tool for water/energy savings and consequent reduction of CO2 emissions.